DETEKSI BAKTERI ENTEROHEMORRHAGIC ESCHERICHIA COLI PADA LAWAR MERAH BABI DENGAN MENGGUNAKAN TEKNIK POLYMERASE CHAIN REACTION (PCR) PADA WARUNG DI DENPASAR - Tjoantara, Andien Nikita; Surudarma, I Wayan; Wiryanthini, Ida Ayu Dewi; Sutadarma, I Wayan Gede (E-Jurnal Medika Udayana; Vol 12 No 5 (2023): E-Jurnal Medika Udayana, 2023)
Lawar merah babi is one of the typical Balinese dish made from pork, pork skin, some vegetables, coconut, various spices, and fresh blood as red colour. The processing of lawar still very traditional. In the process of processing and serving lawar merah babi, the sellers pay less attention to hygiene such as the materials that contaminated with bacteria, personal hygiene, and unclean cooking equipment. If it is not processed properly and hygienically, it is likely to be contaminated with Escherichia coli bacteria which if consumed will be pathogenic to cause diarrhea. This study aims to determine the presence of Escherichia coli bacterial contamination, especially the Enterohemorrhagic Escherichia coli pathotype on lawar merah babi that sold in stalls in Denpasar with the PCR technique. This research is a descriptive study with a cross sectional research design. The sampling technique used cluster purposive sampling technique with a total sample of 13 samples taken at stalls in Denpasar. All samples were examined at the Integrated Biomedical Laboratory, Department of Biochemistry, Faculty of Medicine, Udayana University. The research procedure starts from lawar merah babi was isolated for protein with a 0.6 probe and then DNA was isolated using a DNA isolation kit (cell lysis solution, nuclear lysis solution, protein precipitation solution, DNA rehydration solution). After that, EHEC was detected using stx-1 and stx-2 as target genes using PCR technique. Of the 13 samples studied, the results obtained did not detect any EHEC pathotype in all samples of the lawar merah babi.